A review of environmental occurrence, toxicity, biotransformation and biomonitoring of volatile organic compounds - Li, Adela Jing; Pal, Vineet Kumar; Kannan, Kurunthachalam (Environmental chemistry and ecotoxicology, 2021)
Volatile organic compounds (VOCs) encompass hundreds of high production volume chemicals that have been used in a wide range of household and industrial products. Widespread use of products that contain VOCs resulted in their ubiquitous occurrence in the environment, with elevated concentrations frequently found in indoor environments. Human exposure to VOCs is pervasive and has been a topic of concern, due to the mutagenic, neurotoxic, genotoxic, and carcinogenic potentials of these chemicals. Although several previous articles described toxic effects of VOCs, relatively less is known on their human exposure and body burdens. VOCs have been determined in human breath condensate, blood, feces, and urine. This review updates the information on the environmental occurrence, toxicity, sources and pathways of human exposure, metabolism and elimination, and biomonitoring of exposure to VOCs. Indoor air is a major source of human exposure to VOCs. Higher atmospheric concentrations of VOCs have been reported in Asian countries than in North American and European countries. Elevated concentrations of four widely studied VOCs namely, benzene, toluene, ethylbenzene and xylene (BTEX) were reported in air from newly constructed or renovated homes (1.3–350 μg/m3) and e-waste workshops (2.45–3,10,000 μg/m3). BTEX were also found in consumer products such as shoe polish, whiteout, leather cleaner and ink at notable concentrations (e.g., ~92,600 μg/g). Traditional methods of exposure assessment of VOCs entailed measurement of these chemicals in indoor air and determination of inhalation exposure dose. SStudies on VOC exposure assessment mainly focused on occupationally exposed individuals. Recent developments in biomonitoring of urinary metabolites of VOCs present accurate assessment of exposures and internal body burdens. Biomonitoring studies of VOCs offer novel biomarkers for the assessment of airway inflammation, lung injury, neurological disorders, immune dysfunction and cancers in populations. Considering the very high production volume (at billions of pounds annually), known toxicity, and widespread human exposures, significance of VOCs in eliciting adverse health effects in populations will be a subject of increasing public health concern for years to come. [Display omitted] •VOCs are found at higher levels in indoor air (10s to 100s of μg/m3 ) than in outdoor air.•Besides carcinogenicity, VOCs are potent central nervous system toxicants.•VOCs are metabolized quickly and yield several toxic metabolites that are excreted in urine.•Up to 38 VOC metabolites can be measured in urine at concentrations of hundreds to thousands of ng/mL.•Urinary VOC metabolites are valuable biomarkers to link health effects of these chemicals.